(Trans)cultural training in the teaching-learning process of Teletandem: an experience report analysis - MENEZES , Remerson Bezerra; DA SILVA , Guilherme Mariano Martins; FUNO , Ludmila Andreu Belotti (The ESPecialist, 2022)
The present work discusses the (trans)cultural training in the teaching-learning process of a Teletandem interagent in the context of URCA’s Teletandem program, which took place through the partnership between URCA and Georgetown University. The discussion focuses on the interagent’s experience report analysis and is theoretically guided by the work of Funo (2015), a study that portrays the issues of cultural identities presented in mediation sessions, thus aiming at understanding the correlation between transculturality and the role of the mediator. It also uses the work of Telles, Zakir and Funo (2015), since the article addresses cultural learning through an interaction session between a Brazilian and an American showing the methodological procedures of the program in this relationship, mirroring the empirical relationship presented in this article. Thus, this work is based on excerpts analyzed and taken from reports that were produced with Teletandem interaction sessions, whose main objective aimed to demonstrate, how this process contributed to the transcultural training of the interagent. The initial hypothesis of this study is that the teaching-learning process of the individual interagent in Teletandem developed language skills and contributed to his cultural training.